Effect of birth month on physical fitness of soccer players (Under-15) according to biological maturity - Fragoso, I.; Massuca, L. M.; Ferreira, J. (International Journal of Sports Medicine, 2015)
This study aims to clarify the relationship between the birth quarters, biological maturity and physical fitness (PF) in Under-15 youth soccer players. Each participant (n=133) was an Under-15 player from a top-elite soccer academy. The data collection period lasted 8 years (from Under-15 2002/2003 to 2009/2010 season). The athletes` birth dates were recorded and organized by birth quarters (Q1, first; Q2, second; Q3, third; Q4, fourth) and by semesters (S1, first; S2, second). Additionally recorded were each athlete`s biological maturity (skeletal age, SA), anthropometric profile (stature; body mass; thigh, calf and upper arm girths), and fitness profile (10-m and 30-m sprint times; SJ; CMJ; shuttles in YYIR Test). Significant differences were found for (1) decimal age and SA by quarters (Q4-Q1, Q2) and semesters; and (2) stature (Q3-Q1, Q2, Q4; S1-S2), body mass (Q1-Q3; S1-S2), thigh girth (S1-S2), SJ (Q1-Q2) and sprint time (Q4-Q1, Q2; S1-S2). When maturity was considered as covariate all PF variables, with exception of SJ (Q1-Q2) and 10-m sprint time (S1-S2), were very similar among the studied groups. These findings suggest that (1) seasonal birth effect may result from the observed biological maturation differences, and (2) athletes may have been chosen due to their PF attributes.